SMALL & MEDIUM ENTERPRISES in Malaysia potential and prospects (Ministry of Higher Education, 2010)
This is abook about Small and Medium Enterprises (SMEs) in Malaysia. It began as a reserch programme commissioned by the Ministry of Higher Education to investigate SMEs in different sectors of the economy, with the chief aim of ascertaining the critical success factors (CSFs) that typically lead to success or failure. Selected industries were studied individually by research groups from eight Malaysian public universities, and the original research reports were reworked in the from of the chapters of this book.